In situ scanning electron microscopy analysis of effect of temperature on small fatigue crack growth behavior of nickel-based single-crystal superalloy. (November 2019) - Liang, Jiecun; Wang, Zhen; Xie, Hongfu; Shi, Huiji; Li, Xide
Highlights: An in situ SEM high-temperature (<1000 °C) mechanical testing system was developed. The transition behavior of crack propagation mode from room temperature to 980 °C was analyzed. The plastic zone size was used to characterize the small fatigue crack growth behavior. The growth rate of the crystallographic propagation mode was higher than that of the non-crystallographic mode. Abstract: In situ observation and measurement of the high-temperature deformation of advanced hot-section materials using scanning electron microscopy (SEM) is beneficial for understanding their microscopic failure mechanisms. Through in-situ measurement and subsequent analysis, crack nucleation site, growth rate and propagation behavior can be determined as well as the interaction between crack and microstructure, such as inclusion, pore or grain boundary. However, these measurements are challenging above 700 °C as the SEM images are severely degraded by the thermal electron emission. In this work, an in situ mechanical testing system for extremely high temperatures (up to 1000 °C) inside an SEM was developed and used to investigate the small fatigue crack growth behavior of a nickel-based single-crystal superalloy from room temperature to 980 °C. The fatigue crack propagation modes and growth rates were investigated at different temperatures. The mechanism of the propagation mode transition was discussed in detail. Conventional Paris law was found no longer capable of characterizing the growth behavior of small crack. Subsequently, with the help of the digital image correlation technique, plastic zone size of the crack tip was obtained, and it was found that it could characterize the growth behavior of the small crack.